Warm-up optimizes postural control but requires some minutes of recovery - Paillard, T.; Kadri, M. A.; Nouar, M. B.; Noé, F. (The Journal of Strength and Conditioning Research, 2018)
The aim was to compare monopedal postural control between the dominant leg (D-Leg) and the nondominant leg (ND-Leg) in pre- and post-warm-up conditions. Thirty healthy male sports science students were evaluated before and after a warm-up exercise (12 minutes of pedaling with an incremental effort on a cycle ergometer with a controlled workload). Monopodal postural control was assessed for the D- and ND-Legs before and immediately, 2, 5, 10, and 15 minutes after the warm-up exercise, using a force platform and calculating the displacement velocity of the center of foot pressure on the mediolateral (COPML velocity) and anteroposterior (COPAP velocity) axes. No significant difference was observed between the D-Leg and ND-Leg for both COPML and COPAP velocity in all the periods. In comparison with pre-warm-up, COPML decreased after 15-minute and 10-minute recovery periods for the D-Leg and the ND-Leg, respectively (p < 0.05), whereas COPAP decreased after 10-minute and 15-minute recovery periods (p < 0.001; p < 0.01, respectively) for the D-Leg, and after a 10-minute recovery period for the ND-Leg (p < 0.001). The warm-up optimized monopedal postural control but did not make it possible to distinguish a difference between the D-Leg and the ND-Leg. Some minutes of recovery are required between the end of the whole-body warm-up exercise and the beginning of the postural test to optimize postural control. The optimal duration of recovery turns out to be about 10-15 minutes.